2008
DOI: 10.1243/09544054jem848
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design of partially tapered rectangular thin-walled tubes in axial crushing

Abstract: Straight and tapered thin-walled tubes of rectangular cross-section have been well established as impact energy absorbers under axial loading. This paper investigates the energy absorption capacity and peak transmitted load of partially tapered rectangular tubes. It is shown that these characteristics are notably affected by such design variables as the taper angle and the length of the tapered section. A simulation-based approach is proposed for the fast determination of the optimum geometry of partially tape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In the other hand, Structural optimization is also being interest nowadays to seek for the optimal design. Latest optimal design works are found to seek for multi-comer columns [31], foam-filled beam , conical frusta [38], partially tapered rectangular tubes [39], and multi-cell sections [40].…”
Section: Energy Absorber 41 Axial Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other hand, Structural optimization is also being interest nowadays to seek for the optimal design. Latest optimal design works are found to seek for multi-comer columns [31], foam-filled beam , conical frusta [38], partially tapered rectangular tubes [39], and multi-cell sections [40].…”
Section: Energy Absorber 41 Axial Loadingmentioning
confidence: 99%
“…Yang & Qi [51] and Djamaluddin et al [52] studied on conventional tube filling with filler, both result showed the filled tube works better than the empty tube. In addition, a multi-objective optimization design (MOD) method was employed for the crashworthiness design of multi-cell thin-walled tubes [39,[53][54]. The study shows that conical tube has ability to withstand oblique impact as effectively as axial impact and energy absorption capability of filled tube is better compared to empty tube.…”
Section: Oblique Loadingmentioning
confidence: 99%
“…Thin-walled structures with different cross-sectional shapes have obviously differences on the mechanical behavior. From single tube to multiple tubes, configuration such as square tube [ 10 , 11 ], circular tube [ 12 , 13 ], rectangular tube [ 14 , 15 , 16 ], pyramidal tube [ 17 ], hexagonal tube [ 18 , 19 ], and conical tube [ 20 , 21 ] have been researched widely. The thin-walled structure with cross-sectional shapes including 12-sided and 16-sided star have also been investigated in previous works [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four simple geometries such as hexagon, octagon, 12-sided, and 16-sided star have been already evaluated from an experimental point of view [6], and the results have shown that an increase in the number of inward corners tends to improve the energy absorption capabilities. Other geometries have also been extensively studied, such as circular [7,8], square [9,10], rectangular [11,12,13], hexagonal [14,15,16], pyramidal [17]and conical tubes [18,19,20]. More recently two novel geometries with different materials (pentagon and cross-type section) have been also investigated [21].…”
Section: Introductionmentioning
confidence: 99%